Comparative Study of the Molecular Characterization, Evolution, and Structure Modeling of Digestive Lipase Genes Reveals the Different Evolutionary Selection Between Mammals and Fishes - Tang, Shu-Lin; Liang, Xu-Fang; He, Shan; Li, Ling; Alam, Muhammad Shoaib; Wu, Jiaqi (Frontiers in Genetics, 2022)
Vertebrates need suitable lipases to digest lipids for the requirement of energy and essential nutrients, however, the main digestive lipase genes of fishes have certain controversies. In this study, two types of digestive lipase genes (pancreatic lipase (pl) and bile salt-activated lipase (bsal)) were identified in mammals and fishes. The neighborhood genes and key active sites of the two-lipase genes were conserved in mammals and fishes. Three copies of PL genes were found in mammals, but only one copy of pl gene was found in most of the fish species, the pl gene was even completely absent in some fish species (e.g. zebrafish, medaka and common carp). Additionally, the hydrophobic amino acid residues (Ile and Leu) which are important to pancreatic lipase activity were also absent in most of the fish species. The PL was the main digestive lipase gene in mammals, but the pl gene seemed not to be the main digestive lipase gene in fish due to the absence of the pl gene sequence and the important amino acid residues In contrast, the bsal gene existed in all fish species, even 2-5 copies of bsal genes were found in most of fishes, but only one copy of BSAL gene was found in mammals. The amino acid residues of bile salt-binding sites and the three-dimensional (3-D) structure modeling of Bsal proteins were conserved in most of the fish species, so the bsal might be the main digestive lipase gene in fish. The phylogenetic analysis also indicated that pl or bsal showed an independent evolution between mammals and fishes. Therefore, we inferred that the evolutionary selection of the main digestive lipase genes diverged into two types between the mammals and fishes. These findings will provide a valuable evidence for the study of lipids digestion in fish.